Technical and biological modifications for enhanced flexor tendon repair - Kim, H. Mike (2010)
Clinical outcomes after intra-synovial flexor tendon repair have been substantially improved over the past two decades through advances in tendon suture techniques and postoperative rehabilitation methods. Nevertheless, complications such as repair site elongation (i.e., gap formation) and rupture continue to occur frequently. Experimental studies have shown that repair site strength fails to increase in the first three weeks following tendon suture. After three weeks, the strength and rigidity of the repair site improves significantly, a process that continues for several months. Formation of a repair site gap during the early rehabilitation period has been shown to considerably delay the accrual of repair site strength over time. Thus, it is of prime importance that the method of tendon suture achieves and maintains a stiff and strong repair site during the early healing interval by maintaining close approximation of the tendon stumps and by stimulating, where possible, the intrinsic repair response. In this review we describe recent efforts to enhance the integrity of the immature repair site. We focus on two major areas of advancement: surgical technique modifications and manipulation of the biologic and biochemical environment.